2019
DOI: 10.18502/ijps.v14i4.1982
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout and Related Factors among Health Sector Employees

Abstract: Objective: Job burnout can cause physical and psychological damage and reduce job efficiency, especially in difficult jobs such as health care fields. This study aimed to assess the association between the level of job burnout and some contributing factors among health care providers in Iran. Method: This study was performed on the data derived from 1807 participants from the first phase of the employees’ health cohort in 2017-2018. The data were collected using as a self-administrated tool utilizing Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…In a cross-sectional study conducted on 208 primary HCPs in Iran, the average score of the participants in emotional exhaustion dimension was 17.19, compared to around 27 in our study (Khosravi et al 2017 ). A large study to assess the level of job burnout among 1,807 HCPs in Iran found that mean scores (± SD) in emotional exhaustion, depersonalization, and personal accomplishment subscales were 8.9 (± 9.0), 23 (± 2.9), and 34 (± 8.6), respectively (Bazmi et al 2019 ); while in our study, these values were much higher: 26.6 (± 7.4), 10.2 (± 2.2), and 27.3 (± 3.9), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study conducted on 208 primary HCPs in Iran, the average score of the participants in emotional exhaustion dimension was 17.19, compared to around 27 in our study (Khosravi et al 2017 ). A large study to assess the level of job burnout among 1,807 HCPs in Iran found that mean scores (± SD) in emotional exhaustion, depersonalization, and personal accomplishment subscales were 8.9 (± 9.0), 23 (± 2.9), and 34 (± 8.6), respectively (Bazmi et al 2019 ); while in our study, these values were much higher: 26.6 (± 7.4), 10.2 (± 2.2), and 27.3 (± 3.9), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study conducted on 208 primary health care providers in Iran, the average score of the participants in emotional exhaustion dimension was 17.19, while in our study the average score was around 27 in this subscale (27). A large study to assess the level of job burnout among 1807 healthcare providers in Iran found that mean scores (±SD) in emotional exhaustion, depersonalization, and personal accomplishment subscales were 8.9 (± 9.0), 23 (± 2.9), and 34 (± 8.6), respectively (28); while in our study these values were much higher: 26.6 (±7.4), 10.2 (±2.2), and 27.3 (±3.9), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organizational support as a form of social support (Ahmed, et al, 2011) should be constantly provided to healthcare staff. Job burnout can lead to physical and psychological obstacles and minimize job efficiency, especially in complicated jobs such as healthcare jobs (Bazmi, et al, 2019). These jobs require sustainability of physical, emotional, and mental efforts; hence, it is associated with exhaustion and fatigue (Demerouti, et al, 2001).…”
Section: Perceived Organizational Support and Job Burnoutmentioning
confidence: 99%